Controlling Mast Cell Activation and Homeostasis: Work Influenced by Bill Paul That Continues Today - Caslin, Heather L.; Kiwanuka, Kasalina N.; Haque, Tamara T.; Taruselli, Marcela T.; MacKnight, H. Patrick; Paranjape, Anuya; Ryan, John J. (Frontiers in Immunology, 2018)
Mast cells are tissue resident, innate immune cells with heterogenous phenotypes tuned by cytokines and other microenvironmental stimuli. Playing a protective role in parasitic, bacterial, and viral infections, mast cells are also known for their role in the pathogenesis of allergy, asthma, and autoimmune diseases. Here we review factors controlling mast cell activation, with a focus on receptor signaling and potential therapies for allergic disease. Specifically, we will discuss our work with FcRI and FR signaling, IL-4, IL-10, and TGF-1 treatment, and Stat5. We conclude with apoptosis and autophagy in healthy mast cells and mastocytosis, as well as potential therapeutics for mastocytosis and allergic disease. Much of these efforts have been influenced by the work of Bill Paul. With many mechanistic targets for mast cell activation and different classes of therapeutics being studied, there is reason to be hopeful for progress in this area.